Development of Accounting Crossword Puzzle Learning Media to Improve Vocational High School Students' Learning Activities - Saputri, Agatha; Nurrahman, Arief; Nugraha, R. Andro Zylio; Juliani, Dian; Achmadi, Caesar Rosyad (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This research is development research (RnD) which aims to improve student learning activities in service company accounting competencies for vocational high school students through the development of accounting crossword learning media. This research was carried out collaboratively over two cycles. The ADDIE model is used to develop learning media with a cycle of analyze, design, develop, implementation and evaluation. Validity tests from 5 experts on the media were carried out to assess the suitability of the media before being implemented in the field. The test continued by looking at the feasibility and practicality responses from teachers and students after cycles I and II were carried out. The research sample used in this study was 144 students and 10 teachers taken using purposive random sampling. The data analysis used is descriptive data analysis with percentages. Based on the results of the expert assessment, it shows that the development of accounting crossword learning media is valid for use in accounting learning. Based on the application of accounting crossword puzzles, there was an increase in learning activities from cycle I to cycle II. Based on daily record data, it shows positive changes in students' attitudes towards the development of accounting crossword puzzle learning media in Vocational High Schools.